Optimizing Legal Strategies: Combating Corruption through Anti-Corruption Education in Universities - Ginanjar, Denda; Purnama, Wandra Wardiansha (Veteran Law Review, 2023)
This research proposes an innovative approach to combating corruption, through anti-corruption education within the university environment. Given the increasing cases of corruption in Indonesia, a preventive approach through education is essential in cultivating a generation that is aware of the negative consequences of corruption. The methodology employed is normative research with a legal and literature analysis approach. The analysis results indicate that anti-corruption education in universities holds significant potential in shaping anti-corruption attitudes and values among students. This finding underscores the urgency of integrating courses that examine corruption issues and ethics into university curricula. Based on these findings, the legal strategy of anti-corruption education in universities plays a significant role in reducing corrupt practices. Strengthening educational content that fosters anti-corruption awareness, along with active collaboration among educational institutions, the government, and society, is considered necessary for implementing this strategy.